Optimalisasi Pesan Dalam Buku Edukasi Pasien Diabetes Melitus Melalui Komunikasi Visual - Tegar Andito; Martanty Aditya (DeKaVe, 2019)
The limited number of healthcare personels affects failure on theraphy. In diabetes mellitus patients accellerates complication risks of micro or macrovascular so constant monitoring must be done. Most diabetes mellitus victims begins their diseases at age 45 or older which their cognitive abilities degrade but education is important for diabetes patients. Most healthcare personels educate their patients verbally. With cognitive abilities degradation of diabetes patients,  verbal communication becomes less effective. To overcome this communication problem, the best way is to communicate with less verbally but more visually. Visual communication in this case becomes an effective communication alternative to deliver educational messages which is easier to understand and minimize communication bias. This booklet design hopefully overcomes existing communication barrier in order to improves life quality of patients.